Perspektif Mahasiswa Perguruan Tinggi Swasta di Daerah Terhadap Perkuliahan Daring - Sumarwoto Sumarwoto (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2020)
This study aims to identify the perspectives of students at private universities in the region towards online lectures. This study uses a quantitative approach with a survey method using google form with 140 respondents from various study programs. Data analysis uses descriptive statistics to describe or describe the data that has been collected. From the results that have been obtained, it can be seen that the constraints of students at private tertiary institutions in the regions have special characteristics, especially in internet connection. Most students live in areas with weak internet connections. This has an effect on the criteria for online media that are interested in private tertiary education institutions in the regions, namely using media that is efficient in quotas, does not need a strong network, and is easy to use.